2(4c-1)-6=3c+7

Simple and best practice solution for 2(4c-1)-6=3c+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4c-1)-6=3c+7 equation:


Simplifying
2(4c + -1) + -6 = 3c + 7

Reorder the terms:
2(-1 + 4c) + -6 = 3c + 7
(-1 * 2 + 4c * 2) + -6 = 3c + 7
(-2 + 8c) + -6 = 3c + 7

Reorder the terms:
-2 + -6 + 8c = 3c + 7

Combine like terms: -2 + -6 = -8
-8 + 8c = 3c + 7

Reorder the terms:
-8 + 8c = 7 + 3c

Solving
-8 + 8c = 7 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
-8 + 8c + -3c = 7 + 3c + -3c

Combine like terms: 8c + -3c = 5c
-8 + 5c = 7 + 3c + -3c

Combine like terms: 3c + -3c = 0
-8 + 5c = 7 + 0
-8 + 5c = 7

Add '8' to each side of the equation.
-8 + 8 + 5c = 7 + 8

Combine like terms: -8 + 8 = 0
0 + 5c = 7 + 8
5c = 7 + 8

Combine like terms: 7 + 8 = 15
5c = 15

Divide each side by '5'.
c = 3

Simplifying
c = 3

See similar equations:

| -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 | | -4+4x=-8 | | 2((x+2)+(x+3))=16 | | n+6=19 | | y=3x-1-4 | | (u+3)(2u-1)=-3 |

Equations solver categories